Halide-ion-assisted synthesis of different α-Fe2O3 hollow structures and their lithium-ion storage properties - Ma, Ruguang (2015)
Various α-Fe2O3 hollow structures, such as wormlike shapes, ellipsoids, and quasicubes, were synthesized successfully by a halide-ion-assisted solvothermal method. The self-assembly assisted by selective absorption of halide ions and Ostwald ripening speeded up by acidic etching commonly determine the final unique structures. The electrochemical performance of the α-Fe2O3 with different structures in reversible lithium-ion storage was investigated, and showed that the hollow Fe2O3 quasicubes exhibit the best cycling performance with a charge capacity of 401.6 mAh g−1 after 100 cycles at 0.2 C. The superior cycling stability and high specific capacity can be ascribed to the higher specific surface area, lower charge-transfer resistance, and adequate alleviation of volume variation.